A Class of Special Hypersurfaces in Real Space Forms. (20th June 2016) - Zhao, Yan; Liu, Ximin
Abstract : We define the generalized golden- and product-shaped hypersurfaces in real space forms. A hypersurface M in real space forms R n + 1, S n + 1, and H n + 1 is isoparametric if it has constant principal curvatures. Based on the classification of isoparametric hypersurfaces, we obtain the whole families of the generalized golden- and product-shaped hypersurfaces in real space forms.